The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1476-4598-9-220
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced survival signaling in lung cancer cells is dependent on their p53 status while its down-regulation by curcumin is independent

Abstract: BackgroundLung cancer is the most lethal cancer and almost 90% of lung cancer is due to cigarette smoking. Even though nicotine, one of the major ingredients of cigarette smoke and the causative agent for addiction, is not a carcinogen by itself, several investigators have shown that nicotine can induce cell proliferation and angiogenesis. We observed that the proliferative index of nicotine is different in the lung cancer cell lines H1299 (p53-/-) and A549 (p53+/+) which indicates that the mode of up-regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 61 publications
2
35
1
Order By: Relevance
“…We have reported that baicalin attenuates pulmonary inflammation by inhibiting NF-κB activation in cigarette smoke-induced COPD rat model (24). In the present study, expression of NF-κB p65 induced by nicotine in A549 cells differed from that in H1299 cells, depending on their p53 status (35). Flavones in Scutellaria dramatically downregulated NF-κB p65 protein expression in both cell types and elevated IκB-α protein expression in H1299 cells.…”
Section: Discussionmentioning
confidence: 44%
“…We have reported that baicalin attenuates pulmonary inflammation by inhibiting NF-κB activation in cigarette smoke-induced COPD rat model (24). In the present study, expression of NF-κB p65 induced by nicotine in A549 cells differed from that in H1299 cells, depending on their p53 status (35). Flavones in Scutellaria dramatically downregulated NF-κB p65 protein expression in both cell types and elevated IκB-α protein expression in H1299 cells.…”
Section: Discussionmentioning
confidence: 44%
“…Some studies show that curcumin affects the expressin of cyclinD1, CDK4, CDK6 and p53, p21, p16 which are related to the regulation of cell cycle (Chen and Xu, 2005;Choudhuri et al, 2005;Divya and Pillai, 2006;Puliyappadamba et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overwhelmingly, mechanisms of action reported for the antitumor efficacy of curcumin in lung cancer cells are via mitochondrial-mediated cell death elicited by an increase in the Bax:B cell lymphoma-2 ratio or by an increase in intracellular reactive oxygen species (ROS) (Chanvorachote et al, 2009;Pongrakhananon et al, 2010;Saha et al, 2010;Wu et al, 2010;Wang et al, 2011Wang et al, , 2013bSahoo et al, 2012;Yang et al, 2012a,b;Liu et al, 2013;Xiao et al, 2013;Chen et al, 2014). Migration and invasive capacity of lung cancer cells may be further decreased by inhibition of matrix metalloprotease expression, decreased nuclear factor-kB, EGFR, Akt, signal transducer and activator of transcription 3, and Cdc42 signaling (Chen et al, 2004(Chen et al, , 2012Lee et al, 2005;Lin et al, 2009Lin et al, , 2012Puliyappadamba et al, 2010;Kaushik et al, 2012;Liu et al, 2013;Yamauchi et al, 2014;Zhou et al, 2013a;Li et al, 2014b). Although drug resistance in lung cancer is a primary cause for therapeutic failure, very few in vitro models of resistance have been used when investigating the potential of curcumin for tertiary interventional strategies.…”
Section: Models For Tertiary Lung Cancer Preventionmentioning
confidence: 99%